Difficult transformation : witnessing the female-to-male transsexual in documentary. - Lee, Yan Wei. (2009)
What is the relationship between transgender ethics and documentary ethics? “Difficult Transformation” addresses this question by demonstrating how four documentaries witness the difficult transformation of the transgender, which in turn evoke non-judgmental ethical responses from the spectator. In the last decade, most films on the subject of female-to-male transgender/transsexual have been almost exclusively and independently produced (albeit loosely) in documentary style instead of fiction. This essay does not seek to uncover the reasons behind placing the transgender subject in documentary. Rather, it explores how documentary filmmaking can provoke the spectator to care for and respond to the transgender without certainty and judgment through the ethical act of witnessing. Through the witnessing of tragedy, ambisexuality death and pornography, these four films call upon the spectator to care for and respond to the transgender without certainty and judgment.